Plasticity in malaria parasite development: mosquito resources influence vector-to-host transmission potential - Oke, Catherine E.; O’Donnell, Aidan J.; Schneider, Petra; Reece, Sarah E. (Frontiers in Malaria, 2024)
Parasites rely on exploiting resources from their hosts and vectors for survival and transmission. This includes nutritional resources, which vary in availability between different hosts and changes during infections. For malaria (Plasmodium) parasites, sexual reproduction (sporogony) and subsequent development of oocysts, which produce sporozoites infectious to the vertebrate host, occurs in the mosquito vector. Mosquitoes in the field exhibit diversity in the amount and type of food they acquire, directly impacting the nutrients available for the replication and development of parasites. While the rate of parasite transmission from vector to host is influenced by the nutritional state of mosquitoes, whether this is due to resource limitation mediating parasite development and productivity is poorly understood. We use the rodent model parasite P. chabaudi and the vector Anopheles stephensi to ask how variation in the amount of sugar and blood provided to malaria-infected mosquitoes affects the potential for parasites to transmit from vector to host. We show that parasites in well-resourced mosquitoes reach a larger oocyst size earlier in development, suggesting faster growth, and have a 1.7-fold higher sporozoite burden than parasites whose vectors only receive sugar. However, this increase in productivity is only partly explained by oocyst development, suggesting that resource availability also impacts the ability of sporozoites to reach the salivary glands. This challenges the assumption of a simple relationship between the number or size of oocysts and onward transmission potential. Furthermore, our findings suggest malaria parasites may actively adjust oocyst growth rate to best exploit nutritional resources; while parasites in low-resourced mosquitoes exhibited a reduction in oocyst burden during sporogony, the remaining oocysts developed more rapidly in the later stages of oocyst development, catching up to reach a similar size to those in well-resourced mosquitoes. Understanding the impacts of resource availability for malaria transmission is urgent given that parasites encounter increasingly variable vectors as consequences of climate change and vector control tools.